2013
DOI: 10.5114/pg.2013.38729
|View full text |Cite
|
Sign up to set email alerts
|

Zenker’s diverticulum: etiopathogenesis, symptoms and diagnosis. Comparison of operative methods

Abstract: Zenker’s diverticulum is an alimentary tract pouch localized in the area of the upper esophageal sphincter. Treatment procedure complications and coexisting diseases constitute a serious diagnostic and therapeutic problem. Characteristic symptoms and signs facilitate differential diagnosis, simultaneously being real patient maladies. There are many treatment procedures leading to pouch septum reduction and decrease of upper esophageal sphincter pressure. After years of experience in operating and endoscopic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 28 publications
1
18
0
5
Order By: Relevance
“…Although characteristic symptoms of ZD are less frequently present in patients compared to dyspepsia, gastroesophageal reflux disease, or irritable bowel syndrome, its presence should always be taken into consideration during differential diagnosis of diseases of the digestive tract [ 5 ]. Family physicians are expected to be able to differentiate between a wide range of illnesses, with less in-depth knowledge in rare conditions, but to be highly competent in managing common diseases [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although characteristic symptoms of ZD are less frequently present in patients compared to dyspepsia, gastroesophageal reflux disease, or irritable bowel syndrome, its presence should always be taken into consideration during differential diagnosis of diseases of the digestive tract [ 5 ]. Family physicians are expected to be able to differentiate between a wide range of illnesses, with less in-depth knowledge in rare conditions, but to be highly competent in managing common diseases [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over time, the diverticulum grows, and patients complain of dysphagia due to oesophagus constriction by the filled diverticulum. Voice alteration and halitosis may also occur [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Literature has shown that esophageal manometry is not routinely required. However, it may help to illuminate the pathogenesis of the diverticulum [ 5 ] HRiM was performed in view of this patient’s atypical presentation of Zenker’s diverticulum at a relative young age compared to the classical presentation in the elderly population. HRiM revealed that the patient had a hypertensive esophagus of Jackhammer esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…Although Zenker's diverticulum is a rare condition, with an incidence rate of 0.01%-0.11% in the American population, it occurs more commonly in elderly patients (>70 years of age). 1 Typical symptoms include dysphagia, regurgitation, chronic cough, aspiration, and weight loss. However, it can remain asymptomatic for years.…”
Section: Answer To: Image 4 (Page 23): Zenker's Diverticulummentioning
confidence: 99%